Hereditary angioedema: Not an allergy - Sanjay Bhivgade; Shubha Melkote; Smita Ghate; H R Jerajani (Indian Journal of Dermatology, 2012)
Hereditary angioedema is a genetic disorder due to a deficiency or malfunction of C1 esterase inhibitor. We herein describe a case of 25-year-old male who presented with swelling over face since one day. There was history of similar episodes since two years with gradual subsidence of swelling without any treatment. Investigations revealed grossly reduced complement C4 and C1 esterase inhibitor level. Patient was diagnosed to have hereditary angioedema type 1 and started on stanozolol 2 mg three times a day with no recurrence in one year of follow-up. Hereditary angioedema resembles angioedema of an allergic reaction. However, the cause is different.